Impact of Product Quality and Brand Perception on Consumer Purchase Choices With Consumer Satisfaction Serving as a Mediating Variable in Thrift Merchandise - Atmaja, Okta Dwi; Irmawati, Irmawati (Program Pascasarjana STIE Amkop Makassar, 2026)
The increased attention of the thrift products indicates that investigating purchase behavior of consumers on product quality, brand reputation and customer satisfaction is substantial. This research attempts to investigate the influences of product quality and brand image to purchasing behavior, as well as mediating variable of customer satisfaction. A statistician method with SEM-PLS approach is used involving 176 respondents to have bought thrift items in Klaten Regency. The findings demonstrate that product quality and brand image have a significantly positive effect on customer satisfaction and purchase behavior. Also, customer satisfaction is found to moderate the relationship between product quality and brand perception towards purchase decision. This suggests that thrift shoppers weigh both a product’s functional features as well as the symbolic meaning and emotional connection linked to brand in the purchasing decision. Practical implications The findings of this study have significant practical implications suggesting that enhancing product quality, brand perception and customer experience may stimulate repurchase intention which lead to long term loyalty.